Pengaruh Kualitas Pelayanan Dan Variasi Menu Terhadap Kepuasan Pelanggan Di Café Hanna Tea Lima Puluh Kota - Abdul Aziz; Hijriyantomi Suyuthie (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to describe the quality of service and menu variations on customer satisfaction in relation to visits and to know the influence of these three variables. This study used quantitative and causal approaches. This study used purposive sampling techniques of non-probability sampling type for sampling. This research instrument uses Google forms arranged based on Likert scales, first tested for validity and reliability. This data was analyzed using SPSS version 26.00. The survey results show that service quality is included in the fairly good category with the appropriate achievement level of 56.2%, menu variations with the appropriate achievement level of 59.8% are included in the fairly good category, and customer satisfaction. the level of achievement of respondents. 54% were in the appropriate category. The effect of service quality (X1) and menu selection (X2) on customer satisfaction (Y) was 28.2%, while the remaining 71.8% was influenced by other factors.